2020
DOI: 10.1364/ome.390482
|View full text |Cite
|
Sign up to set email alerts
|

CO2 laser annealed SiGe core optical fibers with radial Ge concentration gradients

Abstract: CO 2 laser annealing of SiGe core, glass-clad optical fibers is a powerful technique for the production of single-crystal cores with spatially varying Ge concentrations. Laser power, laser scan speed and cooling air flow alter the Ge distribution during annealing. In this work, near-single crystal fibers exhibiting a central axial feature with peak Ge concentration ∼15 at% higher than the exterior of the semiconductor core have been prepared. Preferential transmission of near infrared radiation through the Ge-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…However, solidification kinetics are an important consideration; at sufficiently high cooling rates, diffusion-limited inhomogeneity can be used to drive the formation of useful compositional microstructures [26,27]. Recent work on radially varying semiconductor composition in SiGe fibers [28] is promising for reduction of cladding losses with smaller cores. The pseudo-eutectic systems such as GaSb in Si are another option, but may have high conductivity if residual unbonded Group III or V elements remain, reducing the transparency window.…”
Section: Resultsmentioning
confidence: 99%
“…However, solidification kinetics are an important consideration; at sufficiently high cooling rates, diffusion-limited inhomogeneity can be used to drive the formation of useful compositional microstructures [26,27]. Recent work on radially varying semiconductor composition in SiGe fibers [28] is promising for reduction of cladding losses with smaller cores. The pseudo-eutectic systems such as GaSb in Si are another option, but may have high conductivity if residual unbonded Group III or V elements remain, reducing the transparency window.…”
Section: Resultsmentioning
confidence: 99%
“…The high localization of the laser treatment has opened up other opportunities. For example, Coucheron et al showed that laser processing can help overcome the composition segregation issue in in SiGe core fiber due to the non-equilibrium solidification while graded-index SiGe core fibers have also been realized [61,62]. Fokine et al demonstrated a Bragg grating with a spacing of 20 µm on fiber by introducing strain within the cladding and at the interface between the glass and the core using a femtosecond laser [63].…”
Section: Laser Processingmentioning
confidence: 99%
“…These losses are relatively high compared to their constituent unary counterparts and further improvement is required; likely facilitated through optimisation of the post-processing parameters. The different solidification temperatures of silicon and germanium allow the composition of the alloy to be locally altered by CO 2 laser annealing and Wu et al used the technique to demonstrate radial and axial Ge concentration variations within a SiGe fiber [62,83]. Compositional variations along the fiber's length is a potential route for the fabricating in-fiber diode-like structure, leading to photodetection and solar cell applications, while the radial graded core structure is particular useful for infrared transmission beyond 4 µm as the Gerich region serves as the preferential guiding medium.…”
Section: Semiconductor Alloysmentioning
confidence: 99%
“…(g–i) Adapted with permission. [ 54 ] Copyright 2020, The Optical Society. j) Laser‐induced phase segregation in a GaSb/Si core fiber.…”
Section: Laser‐processed Fiber‐based Photonic Devicesmentioning
confidence: 99%
“…i) XCT image of the longitudinal cross-section showing radially symmetric concentration gradients obtained along the SiGe core. (g-i) Adapted with permission [54]. Copyright 2020, The Optical Society.…”
mentioning
confidence: 99%